New evidence of the importance of faulting in the structure of the Sierras Australes de la Provincia de Buenos Aires - Tomezzoli, R.N. (1998)
The Sierras Australes de la Provincia de Buenos Aires or Sierra de la Ventana are situated in the south part of Buenos Aires province, Argentina, between 37°-39°S and 61°-63°W, and constitute a curved fold and thrust belt with a general northwest strike. They are formed of Precambrian to Permian rocks. The oldest and more intensely deformed rocks out in the western ranges, whereas the younger and less deformed are located in the east. Traditionally, these ranges were considered as an example of pure folding without any associated faulting. In this paper, mesoscale structural sections that prove the importance of faulting in the ranges development are described. On a regional scale, the presence of tectonic contacts between the Lolen Formation (upper Devonian) and Providencia Formation (lower Devonian), and between the latter and the Neposta Formation (lower Devonian) are suggested in Parque Tornquist, Estancia Las Vertientes and at Cerro Tres Picos. Field evidence, suggests that the Pillahunico Ranges are structurally higher than the Ventana Ranges, because of a north-east dipping underthrust.